An appreciative inquiry into foreign national prisoners’ participation in prison activities: The role of language - Croux, Flore (European journal of criminology, 2023)
This article presents the findings of 51 interviews with foreign national prisoners in Flanders (Belgium). Following an appreciative inquiry stance, the aim is to understand how foreign nationals experience (accessibility to) prison activities (for example, education, work, sports activities and worship) and to investigate if and how this differs between foreign-speaking and Dutch-speaking foreign nationals. A thematic analysis of the interviews revealed several components of the activities offered that were perceived by the foreign nationals to be ?working well? and revealed several dreams concerning the activities for foreign nationals. Within each theme considered, similarities and dissimilarities among foreign-speaking and Dutch-speaking foreign nationals are described. This article argues that foreign nationals are confronted with a new pain of imprisonment, namely ?the pain of (non-)participation?. The findings could enable a shift from supply-driven to tailor-made activities for foreign national prisoners.